Perampanel as monotherapy and adjunctive therapy for focal onset seizures, focal to bilateral tonic-clonic seizures and as adjunctive therapy of generalized onset tonic-clonic seizures - Tyrlikova, Ivana; Brazdil, Milan; Rektor, Ivan; Tyrlik, Michal (Expert review of neurotherapeutics, 2019)
Introduction: Perampanel is an antiepileptic drug approved in the USA and Europe as monotherapy and adjunctive therapy for focal onset seizures and as adjunctive therapy for generalized tonic-clonic seizures. Areas covered: This an overview of animal data, pharmacokinetics, and clinical data published on Perampanel indexed in PubMed. Expert opinion: Pharmacological studies suggest that perampanel acts via noncompetitive antagonism of the ionotropic AMPA receptor of glutamate. The efficacy of perampanel has been shown in animal models of epilepsy and Phase II/III clinical trials. Efficacy and safety have been evaluated in the phase III trials of adjunctive treatment of focal epilepsy with median focal onset seizure reduction rates of 23% for 4 mg/d, 26-31% for 8 mg/day, and 18-35% for 12 mg/day. Fifty percent responder rates were 29% for 4 mg/day, 33-38% for 8 mg/day, and 34-36% for 12 mg/day. A pivotal Phase III trial in generalized onset tonic-clonic seizures showed a median seizure reduction by 76.5% (8 mg) versus 38.4% placebo and 50% seizure responder rate of 64.2% versus 30.9% placebo. Perampanel showed good safety and tolerability profile across 2-12 mg doses. Perampanel as a broad-spectrum antiepileptic drug has a potential to be an alternative treatment of multiple types of epileptic seizures.
Keywords: monotherapy; záchvaty; anti-seizure drug; adjunctive therapy; Epilepsy, Generalized; Epilepsies, Partial; AMPA receptor antagonist; Drug Therapy, Combination; antikonvulziva; Seizures; epilepsie parciální; Pyridones; kombinovaná farmakoterapie; zvířata; Humans; Anticonvulsants; generalized tonic-clonic seizures; pyridony; focal seizures; epilepsie generalizovaná; nitrily; lidé; Nitriles; Animals